Promocja polskich towarów zgodnie z przepisami prawa wspólnotowego - Kuźmińska, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
After joining the European Union some Polish programes promoting Polish products had to be changed in order to adjust to European regulations. Programes that use public help have to be opened for producers and products from all European countries. The protection of original, high quality food products, made with traditional methods is in Europe very important and popular. The European Union has created system to protect and promote food products: Protected Designation of Origin, Protected Geographical Indication and Traditional Speciality Guaranteed. This system helps to protect product names from imitation and gives the consumer information about the best food and specific character of the product. In Poland there is a lot of traditional food products that are worth to register. They can become popular beyond national border and also can help to promote regions where they come from. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 227-234